Apolipoprotein E (APOE) genotype and the pesticide chlorpyrifos modulate attention, motivation and impulsivity in female mice in the 5-choice serial reaction time task. (June 2016) - Peris-Sampedro, Fiona; Reverte, Ingrid; Basaure, Pia; Cabré, Maria; Domingo, José L.; Colomina, Maria Teresa
Abstract: Organophosphate pesticides – and chlorpyrifos (CPF) in particular – contribute to a wide range of neurobehavioural disorders. Most experimental research focuses on learning and memory processes, while other behaviours remain understudied. The isoforms of the human apolipoprotein E (apoE) confer different cognitive skills on their carriers, but data on this topic are still limited. The current study was performed to assess whether the APOE genotypic variability differently modulates the effects of CPF on attentional performance, inhibitory control and motivation. Human apoE targeted replacement adult female mice (apoE2, apoE3 and apoE4) were trained to stably perform the 5-choice serial reaction time task (5-CSRTT). Animals were then subjected to daily dietary CPF (3.75 mg/kg body weight) for 4 weeks. After CPF exposure, we established a 4-week CPF-free period to assess recovery. All individuals acquired the task, apoE2 mice showed enhanced learning, while apoE4 mice displayed increased premature and perseverative responding. This genotype-dependent lack of inhibitory control was reversed by CPF. Overall, the pesticide induced protracted impairments in sustained attention and motivation, and it reduced anticipatory responding. ApoE3 mice exhibited delayed attentional disruptions throughout the wash-out period. Taken together, these findings provide notable evidence on the emergence of CPF-related attentional and motivational deficits. Highlights: ApoE2 female mice acquire the 5-CSRTT faster than apoE3 and apoE4. ApoE4 female mice showed impaired inhibitory control in the 5-CSRTT. Dietary CPF ameliorated the poor inhibitory control of apoE4 female mice. Dietary CPF induced protracted attentional impairments in apoE TR female mice. Dietary CPF triggered motivational deficits in apoE TR female mice.